2021
DOI: 10.1302/2058-5241.6.200071
|View full text |Cite
|
Sign up to set email alerts
|

A clinical review of robotic navigation in total knee arthroplasty: historical systems to modern design

Abstract: Robotic-assisted total knee arthroplasty (RA-TKA) has shown improved reproducibility and precision in mechanical alignment restoration, with improvement in early functional outcomes and 90-day episode of care cost savings compared to conventional TKA in some studies. However, its value is still to be determined. Current studies of RA-TKA systems are limited by short-term follow-up and significant heterogeneity of the available systems. In today’s paradigm shift towards an increased emphasis on quality of care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…Firstly, no a priori sample size calculations were obtained. In a previous study, robot-assisted TKA decreased rates of MUA up to 4.5-fold compared with conventional TKA with at least 44 cases of MUA24; this study was unable to reproduce that finding because of an insufficient number of MUAs. Secondly, this was a retrospective analysis, which could allow for selection bias of patient characteristics associated with the choice of implants.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Firstly, no a priori sample size calculations were obtained. In a previous study, robot-assisted TKA decreased rates of MUA up to 4.5-fold compared with conventional TKA with at least 44 cases of MUA24; this study was unable to reproduce that finding because of an insufficient number of MUAs. Secondly, this was a retrospective analysis, which could allow for selection bias of patient characteristics associated with the choice of implants.…”
Section: Discussionmentioning
confidence: 58%
“…Firstly, no a priori sample size calculations were obtained. In a previous study, robotassisted TKA decreased rates of MUA up to 4.5-fold compared with conventional TKA with at least 44 cases of MUA 24 ; this study was unable to reproduce that finding because of an This study highlights the need for further research into the relationship between surgical technique and MUA. Future studies should be directed at having adequate sample sizes, incorporating data from multiple surgeons, and using novel surgical technologies.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 64%
“…48 Despite this was not believed to be clinically relevant until recently, it has now become apparent that component positioning has an important influence at least on short-term clinical outcomes. 49 Indeed, several studies have reported on short-term improved functional outcomes, soft-tissue protection, patient satisfaction, and less surgeon and surgical team fatigue when comparing rTKA with conventional technique. [50][51][52] However, further results to prove the effects on implant survivorship are still required.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advancements in implant designs and surgical techniques, CAS and robot technologies in TAA are underdeveloped compared to total hip and knee replacement [ 43 , 44 ]. CAS and robotic systems enable more precise bony resections and soft tissue balance and have been shown to improve implant position and alignment, lower risk for revision surgery, and improve functional outcomes [ 45 , 46 ].…”
Section: Clinical Applications In Foot and Ankle Surgerymentioning
confidence: 99%